MULTIMODAL DIGITAL STORYTELLING FOR DEVELOPING SPEAKING COMPETENCE AND CRITICAL THINKING SKILL - Sri Ariani (Journal of English Education and Literature, 2026)
In the digital era, English learners are expected not only to communicate effectively but also to demonstrate higher-order thinking skills. MDST integrates various communication modes, including text, images, audio, video, and animation, enabling learners to construct meaningful and engaging narratives. The study aims to examine the effectiveness of MDST in improving students’ oral communication abilities and fostering critical thinking through collaborative and reflective learning activities at the English Education Department of Mandalika University of Education. This research employed a mixed-methods design, combining quantitative and qualitative approaches. The participants consisted of undergraduate students enrolled in an English-speaking course. Quantitative data were collected through speaking performance assessments and critical thinking questionnaires administered before and after the implementation of MDST. Meanwhile, qualitative data were obtained from classroom observations and students’ reflective journals. Quantitative data were analyzed using descriptive statistics and paired-sample t-tests to determine the significance of students’ improvement, while qualitative data were analyzed through thematic analysis to identify emerging patterns related to learners’ experiences and perceptions. The findings reveal that the implementation of MDST significantly improves students’ speaking fluency, pronunciation, vocabulary use, and confidence in expressing ideas. Furthermore, the processes of planning, organizing, evaluating information, and presenting digital stories encourage learners to analyze issues critically, solve problems creatively, and make informed decisions. The integration of technology and storytelling also enhances students’ motivation and active participation in English learning. The study concludes that Multimodal Digital Storytelling serves as an innovative pedagogical approach that effectively promotes both speaking competence and critical thinking skills.